Large loop versus straight‐wire excision of the transformation zone for treatment of cervical intraepithelial neoplasia: a randomised controlled trial of electrosurgical techniques. (17th December 2014) - Camargo, MJ; Russomano, FB; Tristão, MA; Huf, G; Prendiville, W
<x xml:space="preserve">Abstract</x> Objective To compare two electrosurgical techniques, straight‐wire excision of transformation zone (SWETZ) with large loop excision of transformation zone, as a cone procedure (LLETZ‐cone), for the treatment of cervical intraepithelial neoplasia (CIN), when disease is present at the cervical canal. Design Randomised controlled trial. Setting Two public hospitals, one in Rio de Janeiro, Brazil and one in Dublin, Ireland. Population One hundred and three women with indication to treat CIN located at cervical canal. Methods Women were randomised to receive LLETZ‐cone or SWETZ. Outcomes Main outcome was the incidence of complete excision of disease at endocervical margin of the surgical specimen. Secondary outcomes were complete excision at ectocervical and stromal margins, time to complete the procedure, specimen fragmentation, blood loss and death after 1 year. Results Fifty‐two women were allocated to LLETZ‐cone and 51 to SWETZ. Ten women were lost for main outcome because of damaged specimens. Forty‐two women in the LLETZ‐cone group had free endocervical margin versus 43 women in the SWETZ group (relative risk 1.04, 95% confidence interval [95% CI] 0.87–1.25; P = 0.64). For secondary outcomes related to margins, we observed a relative risk of 1.15 (95% CI 0.95–1.39; P = 0.15) for ectocervical free margin. For free stromal margin, the relative risk was 1.07 (95% CI 0.89–1.29; P = 0.47). No death was observed. Conclusions This study was inconclusive; SWETZ and LLETZ‐cone were equally effective to treat endocervical disease, with no difference in protecting against margin involvement. Higher, but not severe, blood loss and longer surgical time were observed in the SWETZ group.